The more data is generating the more Muslims with diabetes are allowed to fast during Ramadan (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2026)
Abstract not available [J Assoc Clin Endocrinol Diabetol Bangladesh, January 2026; 5(1): 01]